Analisis Penggunaan Bahasa Slang pada Masyarakat Baduy Luar - Annisa Dwi Oktaviyani; Silva Azahra; Melawati Melawati; Eneng Liah Khoiriyah; Iim Khairunnisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study uses a descriptive qualitative research method to analyze the variation of slang used by the Baduy local community, Desa Kanekes. The data collected is a data primer, which is collected through fieldwork and data collection through questionnaires. The research also uses a survey method to gather information from 10 local residents, focusing on the use of slang and language in their daily lives. The results show that the majority of residents use slang in their daily lives, with some using it in their daily conversations. The study also identifies three slang variations: